If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(2x+3)=2x+6-(8x+2
We move all terms to the left:
-4(2x+3)-(2x+6-(8x+2)=0
We multiply parentheses
-8x-(2x+6-(8x+2)-12=0
| -1n+1=8-8n | | 123-5k=6k+13 | | 18m+11m+-13m+-15m=12 | | 2t-t=8 | | T=4s+3.68 | | 3*5x+3*2=(-4)*5x+4*2 | | 2d-7d+9d=-16 | | 2x-2(4x-3=6-6x | | J=g/22+0.146 | | t+13/8=5 | | 7x-11x+36=332 | | -3(1-2x)=21 | | 4+n/3=7 | | 14q+18q+-6q+-18q+-13q=-20 | | 2x-5(x-4)=-3+4x-5 | | 7x*3=-4*3x | | 2/x+5=8 | | 7xx3=-4x3x | | x2−8x+7=0 | | 7t-16=5 | | 11g+-g+-11g+-10g=11 | | z÷7-7=3 | | -4+a/2=7 | | -10x-10=-10x+(-10) | | 1/8y-4=-9 | | 25x^2-20x-5=0 | | -5(r+8)=-54 | | 3(5x+2)=-4(5x+2) | | n+2/1=0 | | 12a+2a+2a+3a-11a=8 | | -10x—10=-10x+-10 | | -25=5(g+3) |